CHALLENGES OF DIGITAL EDUCATION DEVELOPMENT AT LAW ENFORCEMENT TRAINING INSTITUTIONS - Spridzans, Martins (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
With the ongoing progress of digital education opportunities, recently the buzz of artificial intelligence law enforcement education processes also requires identification and analysis of evolving phenomena. In order to ensure a safe up-to-date, highly efficient training process law enforcement officials involved in education process need to be competent with current education trends as well as be able to establish future visionary self-developments, be able for timely adaptation and constant exchange of best practices. The main goal of the article is to identify, analyse and summarizes latest EU scale digital education development visions and research results in context of digital learning, artificial intelligence, possible problems, risks and concerns regarding further digital education integration within specific law enforcement education environment. The article includes the identification of problematic areas by using historic research method, particularly from digital education integration learning experiences. At the conclusion of this research future outlooks in harnessing the potential of digital education within law enforcement have been proposed based on analysis of scientific literature, legal documents as well as empirical insights derived from hands-on experience in teaching within law enforcement environment.